Marketing social y su influencia en la conservación ambiental de Playas del cantón General Villamil de la provincia de Guayas - Macas Macas, Odalis Jessenia (2023)
Currently, environmental conservation has become an urgent global concern due to the growing environmental challenges facing our planet. In this context, social marketing emerges as a powerful tool to address these problems by combining marketing strategies with social and environmental objectives. This thesis investigates the relationship between social marketing and environmental conservation, analyzing how marketing strategies can influence people's behaviors and attitudes towards environmental protection. The study begins by exploring the theoretical foundations of social marketing and its evolution from commercial approaches to promoting social causes, including environmental conservation. In summary, it also highlights the importance of measuring the impact of social marketing campaigns on environmental conservation, considering indicators such as community participation, the adoption of sustainable practices and the change in attitudes towards the environment. Limitations and challenges associated with this approach are addressed, such as the authenticity of brands and the need for longterm commitment...........